Previdência social e desigualdade racial no Brasil - Paola La Guardia Zorzin (2008)
This work analyses the redistribution of income generated by the Brazilian Social Security between the Black and the White people. Three distinctive and complementary approaches were used to analyze the issue. The first approach estimates the effect of Social Security on the poverty and the income between the Black elderly and the White ones. The second one examines in which way Social Security transfers economic resources among the Black and the White at the same cohorte, measuring the effects of the insurances rules and the mortality at each race in this transferences. The last one, measures the transference of insurance`s income among the Black and the White at a period concerning their age range. The results indicate that the Social Security decreases the income difference when it comes to race, among elderly, and brought up great part of elderly from the poverty, mainly black elderly. Besides that, the results, when keeping untouchable the actual rules of the Social Security Program, show that the rate of return of the Black people, in terms of life-cycle income, will be bigger than the White ones, indicating the transference of income from the White to the Black ones. That is due to the larger progressive effect of the programs rules applied on the income distribution, relatively to the lower regressive effect of the differentials of mortality. At the period perspective, practically there is no transference of social insurance income among the two racial groups, because the progressive effect of the social insurance rules is compensated for a less proportion of elderly among Blacks. It is possible to conclude that, even though the rules prefer lower rates of return to the White people, these same laws balance the participation of these groups at the Social Security budget, avoiding that, at a certain time, the black contribute more than the income they receive.